PELATIHAN DASAR MENGOPERASIKAN MESIN BUBUT BAGI PEMUDA USIA PRODUKTIF DISTRIK HERAM KOTA JAYAPURA - Joni, Joni; Tosuli, Yohanis Tangke; Siregar, Samuel; Kaiway, Mickael Ruben; Patabang, Djuarensi; Ranteallo, Obet (Jurnal Abdi Insani, 2025)
Technical skills in lathe machine operation are highly demanded in the manufacturing industry, particularly in the production of machine components and other equipment. However, in Heram District, Jayapura City, access to technical training remains limited, resulting in low competitiveness among the local workforce. The lack of training facilities and qualified instructors has become a major obstacle in developing the skills of productive-age youth. Therefore, basic training in lathe machine operation serves as an important step in improving the quality of human resources, particularly for productive-age youth in Heram District, Jayapura City. The objective of this community service program is to equip productive-age youth in Heram District with fundamental skills in lathe machine operation, thereby enhancing their employment opportunities and economic independence. The methods implemented in this program include: identifying training participants who meet the productive-age criteria; providing training facilities and equipment, including lathe machines, safety gear, and training modules; coordinating with competent instructors in the field of machining; delivering the training through both theoretical and practical sessions with a composition of 30% theory and 70% practice; and conducting evaluations through theoretical and practical examinations to assess participants’ competencies after the training. Based on the post-training evaluation results, participants demonstrated a solid understanding of the basic concepts in theory, and most were able to perform basic turning operations accurately. The training was highly relevant to participants’ needs, and the majority expressed satisfaction with the program. The final evaluation concluded that, on average, participants achieved good to excellent scores, with high satisfaction ratings for material delivery, instructor preparedness, practical sessions, and the facilities provided.